Strategi Guru Pendidikan Agama Islam dalam Menanamkan Karakter Kepemimpinan - Zaky, Raihan; Setiawan, Hasrian Rudi (Fitrah: Journal of Islamic Education, 2023)
The modern era demands changes in the world of education, one of which is the quality of graduates. Graduates are required to have many abilities and characters. One of these characters is leadership. The modern era urges graduates to be able to manage, lead, and make decisions quickly, so they can compete. With regard to that, this research aims to analyze the cultivation of leadership character to students, the focus of the research is on the strategy of Islamic religious education teachers. This research was conducted at Al Ulum Medan Junior High School. This research uses qualitative methods, based on descriptive studies. Data collection through observation, interviews and documentation. The informants of this research are Islamic religious education teachers and students. The results showed that the strategy of cultivating leadership character focused on fellow students and the social environment. The strategy of planting it by habituation, exemplary, and cooperation with other teachers. The strategy is realized by teachers providing good examples to students. such as for the discipline of worship time, and encouraging students to worship together. This can have a positive impact in the long run, both in the family and community environment.